THE TRAINING OF THE LAW PROFESSIONAL IN THE LAY UNIVERSITY ELOY ALFARO DE MANABÍ, ECUADOR: A LOOK FROM THE PROFESSIONAL ENVIRONMENTAL PERFORMANCE - Juana de Jesús Ochoa Soledispa; Holger Walfredy Vélez Bailón; Laura Leticia Mendoza Tauler (University of Las Tunas, 2018)
As part of the transformations that take place, today in Ecuador it is expressed that in Higher Education we must work to deploy science and technology as factors for the development of society. The Lay University Eloy Alfaro de Manabí has as part of its mission, a permanent commitment to national development through scientific and social research. His vision highlights the training of specialized professionals with extensive scientific knowledge and skills in the practices for students to perform successfully in their work world. The professional performance has dissimilar manifestations and reflects a scope of interpretation from the ends of Higher Education in Ecuador, with an integrating vision that contributes to a reciprocal interaction with the advances of technology and the changing rhythm of social demands that impact on the world of work. It presents an experience in the Ecuadorian context that aims to solve the shortcomings that law students present in professional training, limit their preparation for the solution of environmental problems during pre-professional practice, so that a look of environmental professional performance is presented. the professional training of students, from Environmental Law. The novelty of the proposal lies in the scientific argumentation of environmental professional performance from establishing new relationships, from the technical-legal, environmental and professional dimension of its pedagogical treatment from a social perspective.